Characteristics of Trypsin Isolated From Intestines Different of Fish and Correlation Toward Trypsin Activity - Nurhayati, Tati; Abdullah, Asadatun; Rahmawati, Septiya; Kurniawan, Riki (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
Trypsin is a protease that breaks protein peptide bonds. Fish intestines canbe used as an alternative raw material for trypsin. Trypsin enzymes from theintestines of different fish species have different characteristics. This studyaimed to determine the characteristics and stability of trypsin enzyme inNaCl extracted from fish intestines based on differences in fish species. Trypsinactivity was optimal at 50 °C and pH 8, with specific activity values of 0.5993U/mg in rabbitfish, 0.3880 U/mg in sharks, and 0.6964 U/mg in flatfish. Themaximum reaction speed (Vmax) was the highest for trypsin from the intestineof rabbitfish (0.2585 mmol/s), followed by flatfish (0.1042 mmol/s), andshark (0.0599 mmol/s). The lowest Km value was obtained for trypsin fromsharks (0.4084 mM), followed by flatfish (1.0253 mM), and rabbitfish (4.5952mM). Trypsin from the intestines of rabbitfish and flatfish was stable in NaClsolution (concentration 5-30%), as it can maintain a relative activity of morethan 50%. In contrast, trypsin extracted from the intestines of milk fish hada relative activity below 21%. The average molecular weights of the threetrypsin enzymes were 26.8, 27.2; and 21.9 kDa, respectively. Differences inthe type of fish affected trypsin enzyme activity. Flatfish are omnivorous,and rabbitfish, as herbivores, have better enzyme activity values than sharks,as carnivores.